American Foreign Service Association records - American Foreign Service Association
Correspondence, memoranda, articles, editorials, essays, newspaper clippings, printed matter, photographs, and other records pertaining to the publication of the American Foreign Service Journal, issued in Washington, D.C., by the American Foreign Service Association, also known as Foreign Service Association. Chiefly editorial correspondence and comment primarily to and from Foreign Service officers of all ranks, State Dept. officials, publishing houses, advertisers, and contributors. Correspondents include Ellis Briggs, Gordon Alexander Craig, Francis Colt De Wolf, Robert H. Estabrook, George F. Kennan, Lewis Rubenstein, Robert Peet Skinner, Henry Serrano Villard, James Russell Wiggins, and Henry M. Wriston.
Professional association of the U.S. Foreign Service dedicated to enhancing the effectiveness of the Foreign Service, promoting understanding of the role of the Foreign Service in America's national security and economic prosperity, and ensuring the maintenance of high professional standards for both career diplomats and political appointees. Founded in 1924.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Briggs, Ellis, -- 1899-1976 -- Correspondence; Craig, Gordon Alexander, -- 1913- -- Correspondence; De Wolf, Francis Colt, -- 1894- -- Correspondence; Estabrook, Robert H. -- Correspondence; Kennan, George F. -- 1904-2005.; Rubenstein, Lewis W. -- 1908- -- Correspondence; Skinner, Robert Peet, -- 1866-1960 -- Correspondence; Villard, Henry Serrano, -- 1900- -- Correspondence; Wiggins, James Russell, -- 1903-2000 -- Correspondence; Wriston, Henry M. -- 1889-1978 -- Correspondence; American foreign service journal; Diplomatic and consular service, American; Diplomatic and consular service, American -- Periodicals